Odpowiedź :
Liczymy x:
[tex]a_1=4,\ a_2=x,\ a_3=9\\\\\dfrac{a_3}{a_2}=\dfrac{a_2}{a_1}\\\\\dfrac{9}{x}=\dfrac{x}{4}\\\\x^2=36\\\\x=-6\quad\text{lub}\quad x=6[/tex]
Ciąg ma być rosnący, więc x = -6 odrzucamy. Stąd:
[tex]\boxed{x=6}[/tex]
Iloraz ciągu:
[tex]q=\dfrac{a_2}{a_1}=\dfrac{6}{4}=\boxed{\dfrac{3}{2}}[/tex]
Siódmy wyraz ciągu:
[tex]a_7=a_3\cdot q^4=9\cdot\Big(\dfrac{3}{2}\Big)^4=9\cdot\dfrac{81}{16}=\boxed{\dfrac{729}{16}}[/tex]
Suma ośmiu początkowych wyrazów:
[tex]S_8=a_1\cdot\dfrac{1-q^8}{1-q}=4\cdot\dfrac{1-(\frac{3}{2})^8}{1-\frac{3}{2}}=-8\cdot\Big(1-\dfrac{6561}{256}\Big)=\dfrac{6561}{32}-8=\boxed{\dfrac{6305}{32}}[/tex]